2020
DOI: 10.1055/s-0040-1716393
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Manifestations of Novel Coronavirus Disease in a 2-Month-Old Infant: A Case Report

Abstract: The main manifestations of novel coronavirus usually include fever and cough. Neurological manifestations have not been properly identified in children. A 65-day-old infant was hospitalized due to poor feeding, weakness, lethargy, and occasional cough. She suffered several seizures during her hospitalization. The brain computed tomography scan depicted a minor hemorrhage. Due to the exacerbation of her condition during hospital stay and the presence of respiratory symptoms in her parents, coronavirus disease w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…After screening by title and abstract, 246 articles proceeded to full-text review. Following full-text review, 126 articles, which reported on a total of 48,332 patients, were included for data extraction and analysis 25–148. The PRIMSA flow diagram is provided in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…After screening by title and abstract, 246 articles proceeded to full-text review. Following full-text review, 126 articles, which reported on a total of 48,332 patients, were included for data extraction and analysis 25–148. The PRIMSA flow diagram is provided in Figure 1.…”
Section: Resultsmentioning
confidence: 99%